Bladder Volume Determination: Two-dimensional Versus Three-dimensional Transvaginal Ultrasound - Ching-Chung Liang; Tien-Yung Wei; Shuenn-Dhy Chang; Ching-Chang Hsieh (Elsevier, 2009)
Objective: To compare the results of in vivo measurement of bladder volume using three-dimensional (3D) ultrasound with that obtained from 2D ultrasound Materials and Methods: Forty female inpatients with benign gynecologic diseases had urinary bladder volume determined by ultrasound before surgery. Each patient was initially scanned using the conventional transvaginal 2D ultrasound method, followed by transvaginal 3D ultrasound, and finally underwent sterilized catheterization to obtain the actual bladder volume. The relationships between actual bladder volume and each of the 2D and 3D scan volumes were determined. Results: The patients' bladder volumes varied from 30 mL to 590 mL. The mean value of the error measurement using transvaginal 2D ultrasound estimation was 15.7%, and the correlation coefficient was 0.90. The mean value of the error measurement using transvaginal 3D ultrasound estimation was −8.48%, with a correlation coefficient of 0.97. Conclusion: Our data showed that the 3D scan tended to underestimate the actual bladder volume, while the 2D scan tended to overestimate it. Nevertheless, each method would suffice as a reliable noninvasive means of predicting actual bladder volume.